An in vivo model of postinflammatory hyperpigmentation and erythema: clinical, colorimetric and molecular characteristics. (1st March 2022) - Vellaichamy, G.; Kohli, I.; Zubair, R.; Yin, C.; Braunberger, T.; Nahhas, A.F.; Nicholson, C.; Mohammad, T.F.; Isedeh, P.; Lyons, A.B.; Nartker, N.; Al‐Jamal, M.; et al.
Summary: Background: Postinflammatory hyperpigmentation (PIH) is a common, acquired pigmentary disorder of the skin associated with significant quality‐of‐life impairment, especially in individuals with skin of colour. Current treatment for PIH is limited, largely due to a poor understanding of disease pathogenesis and the lack of a representative disease model. Objectives: This study is intended to further develop, update and validate our previously designed in vivo model of acne‐induced PIH/postinflammatory erythema (PIE) using different concentrations of trichloroacetic acid (TCA), a medium‐depth chemical peel. Methods: Twenty‐nine patients with skin types II–VI and clinician‐confirmed presence of two or more truncal acne pustules and PIH/PIE were included. On the basis of Investigator's Global Assessment (IGA), clinical polarized photography (CPP), colorimetry and Skindex, we experimentally determined an optimum TCA concentration and assessed our model's ability to exhibit a dose–response relationship between degree of inciting insult and severity of resulting pigmentation. We also performed differential microRNA profiling and pathway analysis to explore the potential of microRNAs as molecular adjuncts to our model. Results: Application of TCA 30% produced lesions indistinguishable from acne‐induced PIH and PIE lesions on the basis of colorimetry data without causing epidermal necrosis. Application of progressively increasing TCA doses from 20% to 30% resulted in concentration‐dependent increases in CPP, IGA and colorimetry scores at all timepoints during the study. miRNA‐31 and miRNA‐23b may play a role in PIH pathogenesis, although further validation is required. Conclusions: Our TCA‐based in vivo model, using TCA concentrations between 20% and 30% with an optimum of 30%, enables the quantitative assessment of the pigmentary response to varying degrees of cutaneous inflammation in a fashion that mirrors natural acne‐induced PIH and PIE.